1978
DOI: 10.1002/path.1711260203
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the rat liver following a single autoprotective dose of 3′‐methyl‐4‐dimethylaminoazobenzene

Abstract: Male inbred Leeds strain rats were given single intragastric doses of 1200 mg/kg of 3'-methyl-4-dimethylaminoazobenzene, autoprotective against liver necrosis and then sacrificed at intervals up to 14 months. About 40 per cent of the animals died, apparently as a result of pancreatic necrosis, between 9 and 13 days after treatment while the remainder survived until they were killed. The liver changes induced included an early intense ductular cell reaction, presistent hepatocellular abnormalities and at later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Our morphological and histochemical investigations confirm that the two lines of ductular cells and hepatocytes remain distinct at all stages of the proliferation of epithelium that follows ligation of the common bile duct in this species and offer no support for the possibility of transformations. Flaks and Flaks (1978) discussed the possibility of two types of ductular cell proliferations with and without carcinogenic potential. Ianoka (1967) and Iwasaki et al (1972) suggested that the oval cells appearing in azo-dye carcinogenesis may be precursors of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our morphological and histochemical investigations confirm that the two lines of ductular cells and hepatocytes remain distinct at all stages of the proliferation of epithelium that follows ligation of the common bile duct in this species and offer no support for the possibility of transformations. Flaks and Flaks (1978) discussed the possibility of two types of ductular cell proliferations with and without carcinogenic potential. Ianoka (1967) and Iwasaki et al (1972) suggested that the oval cells appearing in azo-dye carcinogenesis may be precursors of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%